2019
DOI: 10.1177/1533033819853241
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Nanoparticles as Drug Delivery Systems and Their Potential Role in the Treatment of Chronic Myelogenous Leukaemia

Abstract: Chronic myeloid leukemia is a myeloproliferative disease where cells of myeloid linage display a t(9;22) chromosomal translocation leading to the formation of the BCR/ABL fusion gene and the continuous activation of tyrosine kinases. This malignancy has a peak incidence at 45 to 85 years, accounting for 15% of all leukemias in adults. Controlling the activity of tyrosine kinase became the main strategy in chronic myeloid leukemia treatment, with imatinib being placed at the forefront of current treatment proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 134 publications
(193 reference statements)
0
40
0
Order By: Relevance
“…Gold nanoparticles (AuNPs; authorized by the FDA) are among the most widely utilized inorganic nanoparticles in biomedical applications because of their excellent compatibility with the biological system, small size, reduced toxicity, simplicity of surface tailoring, and controlled drug release properties [23]. Although AuNPs are effective in cancer treatment, they are subsequently removed by the reticular endothelium system, particularly macrophages, restricting their use.…”
Section: Introductionmentioning
confidence: 99%
“…Gold nanoparticles (AuNPs; authorized by the FDA) are among the most widely utilized inorganic nanoparticles in biomedical applications because of their excellent compatibility with the biological system, small size, reduced toxicity, simplicity of surface tailoring, and controlled drug release properties [23]. Although AuNPs are effective in cancer treatment, they are subsequently removed by the reticular endothelium system, particularly macrophages, restricting their use.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, many studies have demonstrated the effective therapeutic performance of nanotechnology-based delivery systems [26][27][28][29] . Despite the favorable surface-to-volume ratio of these nanomaterials, instability in vivo and inferior biocompatibility limited their use for in vivo applications 30,31 . Furthermore, typical characteristics of passive drug release mechanisms from these systems do not allow for modifications in response to temporally changing therapeutic needs commonly required in chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Various synthetic protein delivery systems such as lipid- or polymer-based nanocarriers have been developed and tested over the years. These include liposomes, polymer nanoparticles, polymersomes (stable polymeric vesicles, prepared using amphiphilic block polymers of different molecular weights [ 8 ]), micelles (formed by spontaneous arrangement of amphiphilic block copolymers in aqueous solutions [ 9 ]), nanogels (hydrogels with a three-dimensional tunable porous structure and a particle size in the sub-micrometer range [ 10 ]), and inorganic nanoparticles (such as carbon nanotubes and silver/gold/magnetic/ZnO/CuO-based nanoparticles [ 11 ]). In addition, protein delivery systems contain cell-penetrating peptides (CPPs), also called protein-transduction domains (PTDs) as carriers [ 12 ].…”
Section: Cell-penetrating Peptides (Cpps) For Cellular and Intracellular Deliverymentioning
confidence: 99%